Perceived ease of use and perceived usefulness of MOOC TITAS platform in the era of revolution industri 4.0 - Ab. Halim, Adlina; Othman, Normala; Azri, Norasyikin; M. Samir, Nasrina (Human Resource Management Academic Research Society, 2022)
The Massive Open Online Course (MOOC) platform used in the Islamic and Asian Civilization (TITAS) course is a transformation of new teaching and learning methods that increase students’ interest to deepen their knowledge in civilization and current global issues. This study will measure the level of public university student’s acceptance of perceived ease of use, perceived usefulness and attitude towards the MOOC TITAS platform. The study employed a quantitative approach and was conducted among the first-year students in 19 Malaysian public universities by distributing online questionnaire instruments in the google form. The study used the purposive sampling technique and a total number of 1373 university students from five different zones (North Zone, Central Zone, South Zone, East Zone, and Sabah/Sarawak Zone) were involved as respondents. The value of Cronbach’s Alpha for the pilot test was 0.972 and data were analysed using SPSS 25.0. This study found that public university students have a good level of acceptance of the perceived ease of use, perceived usefulness and attitude towards the MOOC TITAS platform with mean value of 4.0. As a competent and effective platform, the MOOC TITAS platform corresponds to the online learning especially during the Covid-19 pandemic. MOOC platform also provides opportunities for students to have quick access to their lecture notes, activities and assessment regardless of time and location constraints.